KEARIFAN EKOLOGIS DALAM LEGENDA “BUJANG SEMBILAN” (ASAL USUL DANAU MANINJAU) - Yosi Wulandari (Madah: Jurnal Bahasa dan Sastra, 2017)
The Legend of “Bujang Sembilan” is a folktale that tells about the origin of Lake Maninjau along with the nagari retreat in Maninjau. Abnormal conditions of the lake often occur every year which is considered the community associated with “Bujang Sembilan”, namely the existence of Tubo (ammonia) that poison the lake water. In connection with this, this study aims to describe (1) the values expressed in the “Bujang Sembilan” legend consistent with ecological wisdom;and (2) the role that can be played by the physical setting (environment) in the legend of “Bujang Sembilan” legend. This research is a description of qualitative descriptions, data derived from literature studies, research data is a word, phrase, clause, or sentence that is abstracted as an ecological wisdom contained in the text “Bujang Sembilan”. Data were collected by data identification techniques based on literary ecological theory. Thus, it can be concluded that the legend of “Bujang Sembilan” also has a story that contains components ofpower and environment that can be reintroduced. The wisdom of ecological theory is an offer linking nature and literature. It was then used as a creative process material for the creation of literary works offering the inspiration of saving the earth.